Patient compliance with colorectal cancer screening in general practice. - Mant, D; Fuller, A; Northover, J; Astrop, P; Chivers, A; Crockett, A; Clements, S; Lawrence, M (1992)
A randomized controlled trial to test patient compliance with screening for colorectal cancer in association with general practice health checks was carried out in six practices (three urban and three rural). A total of 1588 patients aged 45-64 years were randomized to one of four intervention groups. In the first group patients were posted a Haemoccult test (Kline Beckman) kit. This group was not invited for a health check. In the second group patients were posted the Haemoccult test kit, together with an invitation to attend for a health check. In the third group patients were posted an invitation for a health check, which explained that the patient would be offered the Haemoccult test kit by the nurse at the health check. In the fourth group patients were just invited for a health check. It was found that combining faecal occult blood testing with the health check did not reduce attendance at the health check--43.5% of patients attended when the Haemoccult test kit was offered by the nurse at the health check, 43.6% attended when a test kit was included with the invitation to attend the health check and 42.9% attended when the health check invitation was posted on its own. Overall, compliance with Haemoccult testing was not significantly increased by associating it with a health check (26.2% versus 25.5%) but compliance was higher when the faecal occult blood testing kit was enclosed with the health check invitation than when it was offered at the health check (31.7% versus 20.6%, P less than 0.001). It is easier and cheaper to combine various screening procedures. Although the overall use of the Haemoccult test in the study population was low, there is no reason why the relatively higher compliance rate obtained on posting the test kit with a health check invitation cannot be achieved in previously unscreened populations with higher expected compliance rates. However, faecal occult blood screening for colorectal cancer should not be undertaken on a population basis until its effectiveness in reducing mortality has been proven by randomized trial.